Etiological Approach to Understanding Recanalization Failure in Intracranial Large Vessel Occlusion and Thrombectomy: Close to Embolism but Distant From Atherosclerosis - Lee, Seong-Joon; Park, So Young; Hong, Ji Man; Choi, Jin Wook; Kang, Dong-Hun; Kim, Yong-Won; Kim, Yong-Sun; Hong, Jeong-Ho; Kim, Chang-Hyun; Yoo, Joonsang; Nogueira, Raul G.; Hwang, Yang-Ha; et al. (Frontiers in Neurology, 2021)
Introduction: In patients with intracranial large vessel occlusion (LVO) who undergo endovascular treatment (EVT), recanalization failure may be related to intracranial atherosclerotic stenosis (ICAS). We evaluated whether the risk factors of recanalization failure could possibly be a marker of ICAS among various types of LVO. Methods: From a multicenter registry, patients with middle cerebral artery M1 segment occlusions who underwent thrombectomy within 24 h were included. Based on the on-procedure and post-procedure angiographic findings, patients were classified into embolic, ICAS-related, tandem occlusion, and recanalization failure groups. Recanalization failure was defined if the occluded vessel could not be recanalized by stent retrieval, contact aspiration, or local lytics treatment. Risk factors, imaging markers, and EVT methods were compared between groups. Results: Among 326 patients, 214 were classified as embolism, 76 as ICAS, 16 as tandem, and 20 as recanalization failure. The group with recanalization failure showed higher scores on the National Institutes of Health Stroke Scale (NIHSS) (median, 16.0 vs. 14.5 vs. 14.0 vs. 17.0, p = 0.097), frequent atrial fibrillation (59.3 vs. 18.4 vs. 0 vs. 40.0% p < 0.001), and elevation in erythrocyte sedimentation rate (ESR) (14.5 ± 15.7 vs. 15.0 ± 14.1 vs. 21.2 ± 19.5 vs. 36.0 ± 32.9, p < 0.001) among the groups. The rate of computed tomography angiography-based truncal-type occlusion in recanalization failure group was not as high as that in the ICAS group (8.1 vs. 37.5 vs. 0 vs. 16.7%, p < 0.001). Balloon guide catheters (BGC) were less frequently utilized in the recanalization failure group as compared to their use in the other groups (72.0 vs. 72.4 vs. 62.5 vs. 30.0%, p = 0.001). In the multivariable analysis, initial higher NIHSS [odds ratio (OR), 1.11 95% confidence interval (CI), 1.01–1.22 p = 0.027], higher ESR (OR, 1.03 CI, 1.01–1.05 p = 0.006), and non-use of BGCs (OR, 3.41 CI, 1.14–10.17 p = 0.028) were associated with recanalization failure. In M1 occlusions, the predominant mechanism of recanalization failure was presumed to be embolic in 80% and due to ICAS in 20%. Conclusion: The analysis of recanalization failures does not suggest an underlying predominant ICAS mechanism. Sufficient utilization of thrombectomy devices and procedures may improve the rates of recanalization.